ETHNOBOTANICAL STUDY OF TRADITIONAL MEDICINAL PLANTS AND THEIR UTILIZATION IN PASSI VILLAGE, WEST PASSI DISTRICT, BOLAANG MONGONDOW REGENCY - Latip, Irwan; Satiman, Utari; Djarang, Rievo (Universitas Negeri Manado, 2025)
Ethnobotany is the study of the relationship between plants and humans, including the use of plants by local communities. Traditional medicinal plants are plants that are often used by local communities for their health benefits. This study aims to describe the types of medicinal plants used and how they are processed using traditional methods in the village of Passi, West Passi subdistrict, Bolaang Mongondow district. This research is descriptive qualitative with an interview method and descriptive analysis technique. The results of this study show that there are 37 types of medicinal plants used with a total of 23 families found. The methods of processing traditional medicinal plants are: boiling, squeezing, soaking, pounding, and not processing. The most commonly used processing method is boiling, with 24 types of medicinal plants using this method. The parts of the plants that are most commonly used are: stems, fruits, flowers, leaves, roots, gel, sap, rhizomes, and tubers. The most commonly used parts are leaves, rhizomes, and fruits.